2014
DOI: 10.1371/journal.pone.0093415
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Subtype A Gag Variability and Epitope Evolution

Abstract: ObjectiveThe aim of this study was to examine the course of time-dependent evolution of HIV-1 subtype A on a global level, especially with respect to the dynamics of immunogenic HIV gag epitopes.MethodsWe used a total of 1,893 HIV-1 subtype A gag sequences representing a timeline from 1985 through 2010, and 19 different countries in Africa, Europe and Asia. The phylogenetic relationship of subtype A gag and its epidemic dynamics was analysed through a Maximum Likelihood tree and Bayesian Skyline plot, genomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
8
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 31 publications
5
8
1
Order By: Relevance
“…This is significantly different from what was reported in literature and the HIV-1 sequence database [911]. Analysis of all available partial sequences in the database showed that only 2.6% of viral sequences were A1/G recombinant (excluding CRF02 sequences).…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…This is significantly different from what was reported in literature and the HIV-1 sequence database [911]. Analysis of all available partial sequences in the database showed that only 2.6% of viral sequences were A1/G recombinant (excluding CRF02 sequences).…”
Section: Discussioncontrasting
confidence: 88%
“…A number of subtypes and circulating recombinant forms (CRFs) have been reported in Pakistan [911], but no nationwide surveys were performed to systematically study distribution of HIV-1 subtypes and recombinants in the country. Examination of sequences available from the Los Alamos HIV Sequence Database (www.hiv.lanl.gov) showed that subtype A1 was most reported (84.3%), while subtype B, CRF02, A1/G recombinant and others accounted for 8.7%, 2.0%, 2.6% and 2.4%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31] To obtain an estimate of the probability of the future cooccurrence of major-minor mutations, we performed Shannon entropy analysis, which measures the probability of acquiring mutations in a given set of genomic sequences. 22 This analysis revealed that certain regions of protease gene sequences in our study cohort exhibited high entropy, indicating a higher probability of the later occurrence of mutations. The region 1-90 (HBX2 amino acids 20-50), which contained five high entropy patches (Fig.…”
Section: Discussionmentioning
confidence: 64%
“…This is consistent with previous reports on HIV subtypes in Kenya, where subtype A has been shown to be the most common HIV subtype. [20][21][22][23] The second most common viral subtype was D with a prevalence of 22%. This is also consistent with previous studies, where subtype D has been reported to be the second most prevalent subtype in Kenya (www.hiv.lanl.gov/).…”
Section: Discussionmentioning
confidence: 99%
“…To examine HIV transmission networks in FSU countries, 2705 publicly available HIV-1 subtype A pol sequences were downloaded from the Los Alamos HIV Sequence Database (data available as of April 3, 2016) for thirteen countries: Armenia (2009), Azerbaijan (2001–2002), Belarus (1997–2014), Estonia (2001–2010), Georgia (1998–2003), Kazakhstan (1997–2013), Kyrgyzstan (2002–2010), Latvia (1998–2008), Lithuania (1997–2007), Moldova (1997), Russia (1986–2015), Ukraine (1996–2012), and Uzbekistan (1999–2002). These sequences were aligned, edited, and used for the construction of phylogenetic tree as described elsewhere [ 14 ] http://journals.plos.org/plosone/article?id=10.1371/journal.pone.0093415 . Briefly, the sequences were aligned and edited using the software MEGA6 .…”
Section: Methodsmentioning
confidence: 99%